Hoop tensile strength behaviour between different thicknesses E-glass and S-glass FRP rings - Bobba, Sujith; Leman, Zulkiflle; Zainudin, Edi Syams; Salit, Mohd Sapuan (AIMS Press, 2019)
This paper reports the split disk test (as in ASTM D 2290) modified to characterize the stress–strain behaviour of two different GFRP rings using a simple specimen preparation methodology. To compare the split disk ultimate strains, GFRP confined glass fiber rings made of different thicknesses, i.e., 1.75 mm, 2.50 mm and 3.25 mm were tested under uni-axial tensile tests after being wrapped with E-glass and S-glass GFRP fabrics. The results obtained from the modified split-disk tests on E-glass composites were compared with the results obtained from S-glass composites. In addition, the split-disk tests of selected composite specimens were simulated using a finite element method. Strain efficiency factors were then determined for design applications which are in good agreement with the experimental data.